2019
DOI: 10.30802/aalas-cm-18-000053
|View full text |Cite
|
Sign up to set email alerts
|

Ketamine Tolerance in Sprague–Dawley Rats after Chronic Administration of Ketamine, Morphine, or Cocaine

Abstract: Ketamine is one of the most commonly used anesthetics in human and veterinary medicine, but its clinical effectiveness is often compromised due to tolerance to its anesthetic effects. Although ketamine tolerance has been demonstrated in a number of behavioral measures, no published work has investigated tolerance to ketamine's anesthetic effects other than duration of anesthesia. In addition, a reported practice in anesthesiology is to alter anesthetic doses for procedures when the patient has a history of dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It is well known that repeated ketamine use leads to physiological tolerance in the context of its anesthetic properties. 37 However, it is not well studied whether cardiovascular response, nor reduction in depressive symptoms, are subject to increasing dose requirements for the same physiological or psychological impact. Although in the current study average change in systolic blood pressure gradually declined with each subsequence infusion for responders, there seemed to be no coherent pattern to average blood pressure response for subsequent infusions in non-responders.…”
Section: Figurementioning
confidence: 99%
“…It is well known that repeated ketamine use leads to physiological tolerance in the context of its anesthetic properties. 37 However, it is not well studied whether cardiovascular response, nor reduction in depressive symptoms, are subject to increasing dose requirements for the same physiological or psychological impact. Although in the current study average change in systolic blood pressure gradually declined with each subsequence infusion for responders, there seemed to be no coherent pattern to average blood pressure response for subsequent infusions in non-responders.…”
Section: Figurementioning
confidence: 99%
“…Other papers demonstrate animals chronically given ketamine that required increased doses of ketamine to reach the target anesthetic plane. Moreover, animals had a shorter duration of anesthesia [86,88]. Surprisingly, rats pretreated with intraperitoneal morphine at a dose of 5.6 mg/kg demonstrated cross-tolerance to ketamine's anesthetic effects [88].…”
Section: Tolerancementioning
confidence: 99%
“…Moreover, animals had a shorter duration of anesthesia [86,88]. Surprisingly, rats pretreated with intraperitoneal morphine at a dose of 5.6 mg/kg demonstrated cross-tolerance to ketamine's anesthetic effects [88].…”
Section: Tolerancementioning
confidence: 99%
“…The reasons for these mixed outcomes are unclear and might include higher treatment resistance levels 58 , chronic history of depression 58 , ineffective dosing, and possible tolerance-like phenomena 55,58,59 . For example, Sprague-Dawley rats develop tolerance to repeated administration of anesthetic doses of ketamine, possibly arising as a result of receptor desensitization, reduction of receptor density, or increased induction of metabolizing enzymes 60 . Also, a recent animal study comparing the effects of a single and repeated treatment of ketamine demonstrated the lack of antidepressant-like effectiveness of long-term administration 61 , hypothesizing to result from the detrimental effects of the parvalbumin interneurons loss in the prefrontal cortex after repeated treatment 62 and/or possible metabolic side effects.…”
Section: Effects Of Repeated Ketamine Vs Placebomentioning
confidence: 99%